2020
DOI: 10.1029/2019gc008766
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Anisotropy and Mantle Flow in the Sumatra Subduction Zone Constrained by Shear Wave Splitting and Receiver Function Analyses

Abstract: To systematically investigate seismic azimuthal anisotropy in the Sumatra subduction zone and probe mantle dynamics associated with the subduction of the Australian Plate beneath the Sunda Plate, a total of 169 pairs of teleseismic XKS (including PKS, SKKS, SKS) and 115 pairs of local S splitting parameters are obtained using broadband seismic data recorded at ~70 stations. Additionally, crustal anisotropy in the overriding Sunda Plate is measured by analyzing the moveout of P‐to‐S conversions from the Moho us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Advective upwelling of hot material through the slab window can lead to reduced velocities in the upper mantle, and at the same time depress the d410 due to the higher temperature relative to the ambient mantle in the upper-most MTZ. The slab window in the study area, whose presence is also suggested by a recent seismic anisotropy study based on shear wave splitting analysis (Kong et al, 2020), is probably associated with the IFZ and linked with the feeder system of the Toba supervolcano (Koulakov et al, 2016;Liu et al, 2018).…”
Section: Thermal Upwelling Through a Slab Windowsupporting
confidence: 66%
“…Advective upwelling of hot material through the slab window can lead to reduced velocities in the upper mantle, and at the same time depress the d410 due to the higher temperature relative to the ambient mantle in the upper-most MTZ. The slab window in the study area, whose presence is also suggested by a recent seismic anisotropy study based on shear wave splitting analysis (Kong et al, 2020), is probably associated with the IFZ and linked with the feeder system of the Toba supervolcano (Koulakov et al, 2016;Liu et al, 2018).…”
Section: Thermal Upwelling Through a Slab Windowsupporting
confidence: 66%
“…(2016) inferred a tear in the slab beneath the Toba caldera to interpret the abovementioned low‐velocity anomalies and high VP/VS ratios. A recent study of seismic anisotropy also indicated the presence of a slab tear beneath Toba caldera (Kong et al., 2020). Their shear wave splitting measurement reflect both lateral and vertical distributions of anisotropy beneath the Toba caldera and surrounding areas (Kong et al., 2020).…”
Section: Discussionmentioning
confidence: 95%
“…A recent study of seismic anisotropy also indicated the presence of a slab tear beneath Toba caldera (Kong et al., 2020). Their shear wave splitting measurement reflect both lateral and vertical distributions of anisotropy beneath the Toba caldera and surrounding areas (Kong et al., 2020). These anisotropy patterns are attributed to mantle flow that enters the mantle wedge through the slab window resulting from the slab tear.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several seismic anisotropy investigations have been conducted in the central Sunda Plate and surrounding areas to explore the upper mantle seismic anisotropy and associated mantle deformation (Figure S1; Collings et al., 2013; Di Leo et al., 2012; Hammond et al., 2010; Kong, Gao, Liu, Zhang, et al., 2020; Wang & He, 2020; Xue et al., 2013; Y. Yu et al., 2018). While some SWS studies using local S and XKS (including SKS, SKKS, and PKS) waves suggested that the mantle wedge of the Sumatra subduction zone is generally isotropic (Hammond et al., 2010), trench‐orthogonal azimuthal anisotropy has been observed and attributed to a corner flow system in the mantle wedge using data recorded by two temporary seismic networks (Collings et al., 2013).…”
Section: Introductionmentioning
confidence: 99%